Influence of Cross Media Ownership on Freedm of Expression in Pakistan: Influence of Cross Media Ownership on Freedm of Expression in Pakistan - Alam, Riffat; Haq, Amrat; Ruqayya, (Journal of Peace, Development and Communication, 2021)
The growing trend of cross media ownership is one of the factors that influences media to carry out its public role properly. This study analyzed the influence of cross media ownership on freedom of expression, using propaganda model as a framework to explain journalistic practices. Anecdotal evidence suggests media freedom in Pakistan is under the threat of emerging cross media ownership structures that give priority to political and commercial interests. Using qualitative research technique followed by in-depth interviews method of editors of two leading newspapers and news channels belonging to two media conglomerates, for data collection purpose. This study concludes that cross media ownership didn’t promote diversity of news and media convergence is profit oriented rather than objectivity oriented. The results revealed that content homogeneity, set policy and agenda of media outlet and allocation of subsidies and therefore, cross media ownership influence freedom of expression in Pakistan.